A Corpus-Based Study Of Give, Take, And Make Light Verb Constructions In Mesolectal Malaysian English - Christina Sook Beng, Ong (2023)
This study investigated the structural and aspectual functional patterns of light verb constructions (LVCs) in mesolectal Malaysian English and identified nativised LVCs. LVCs refer to combinations of a semantically “empty” or light verb with a deverbal noun. The three selected light verbs are give, take, and make. A standard or prototypical LVC is made up of a light verb and a deverbal noun preceded by the indefinite article as shown in this sentence, I’ll take a look at her feet myself. Studies examining the use of LVCs in postcolonial Englishes suggest emerging variants such as make good decision may not be idiomatic and may not be acceptable by native speakers. To facilitate this research, a 100-million words general corpus of mesolectal Malaysian English was created. This corpus is known as the Corpus of Malaysian English Forum (CMEF). It consists of threads from Lowyat.NET, a popular Internet forum in Malaysia, representing the mesolectal variety of Malaysian English which is commonly used and nationally intelligible. The British National Corpus (BNC) was used as the reference corpus. The structural analysis reveals that Malaysian English LVCs do not deviate much from the standard structure of LVCs except the overuse of zero-article LVCs.